The Mediating Effect of Social Problem-Solving Between Perfectionism and Subjective Well-Being - Wang, Cheng; Huang, Yisi; Xiao, Yueting (Frontiers in Psychology, 2021)
This study examined the relationship between perfectionism and subjective well-being (SWB) and dimensions of social problem-solving ability. The Almost Perfect Scale-Revised (APS-R), Social problem-solving Inventory-Revised (SPSI-R) and Satisfaction with Life Scale (SWLS) were used to conduct a questionnaire survey of 202 Chinese adults. The results found that: (1) Subjective well-being was significantly negatively correlated with the discrepancy dimension of perfectionism and was also significantly negatively correlated with the negative problem orientation of social problem-solving. (2) The discrepancy dimension reflected in maladaptive perfectionism was significantly positively correlated with the negative aspects of social problem solving (Negative Problem Orientation, NPO; Impulsivity-Carelessness Style, ICS; and Avoidance Style, AS). (3) The negative problem orientation (NPO) dimension in SPSI-R, as a partial mediator, mediated the negative correlation between maladaptive perfectionism and subjective well-being. In conclusion, perfectionism and social problem-solving ability had different degrees of influence on the SWB of Chinese adults, and attention could be paid to dealing with discrepancy and how to reduce negative problem-solving tendency in education and clinical practice.